1981
DOI: 10.1161/01.hyp.3.5.566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium chloride on the blood pressure in two-kidney, one clip Goldblatt hypertensive rats.

Abstract: SUMMARY Tbe effects of potassium loading on blood pressure (BP) and the renln-angiotensin-aldosterone system were investigated in two-kidney, one clip Goldblatt hypertensive rats. Two series of experiments were performed: one was begun just after renal artery constriction, and tbe other, after hypertension had developed. Potassium loading significantly attenuated tbe development of hypertension, and was also able to abate existing renovascular hypertension. In both studies, potassium loading increased fluid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 29 publications
(4 reference statements)
0
29
1
Order By: Relevance
“…24 Similarly, in the twokidney, one clip model of renovascular hypertension, potassium attenuates the degree of blood pressure elevation that develops after renal artery clipping. 3 In humans as well, potassium may decrease the hypertensive response to increased sodium intake. 26 ''* These experimental and epidemiological data suggest that potassium deficiency is etiological in hypertension and, conversely, that increased potassium intake protects against the development of hypertension.…”
mentioning
confidence: 99%
“…24 Similarly, in the twokidney, one clip model of renovascular hypertension, potassium attenuates the degree of blood pressure elevation that develops after renal artery clipping. 3 In humans as well, potassium may decrease the hypertensive response to increased sodium intake. 26 ''* These experimental and epidemiological data suggest that potassium deficiency is etiological in hypertension and, conversely, that increased potassium intake protects against the development of hypertension.…”
mentioning
confidence: 99%
“…In most studies, potassium supplementation has been found to ameliorate hypertension by causing an increase in urinary sodium excretion. 28 ' 30 In contrast, since total body sodium and plasma volume are increased in potassium depletion, 10 the protective effect of potassium depletion is independent of changes in sodium and volume and is related to potassium depletion per se.…”
mentioning
confidence: 98%
“…30 ' 31 Although a protective effect of both potassium depletion and potassium supplementation seems paradoxical, the mechanism of protection of these divergent maneuvers appears to differ. In most studies, potassium supplementation has been found to ameliorate hypertension by causing an increase in urinary sodium excretion.…”
mentioning
confidence: 99%
“…A similar protective effect of potassium was observed in Kyoto spontaneously hypertensive rats (SHR) fed excess sodium, 16 Dahl 17 salt-sensitive rats (Dahl S), and in the two-kidney, one clip Goldblatt model. 18 The mechanisms of both the hypertensive effect of excess dietary sodium and the protective effect of potassium remain unknown.In the quest for initiating factors or "prime movers" in hypertension, 19 exhaustive studies of the relationship between sympathetic neural activity and essential hypertension have been conducted. The topic remains embroiled in controversy.…”
mentioning
confidence: 99%
“…A similar protective effect of potassium was observed in Kyoto spontaneously hypertensive rats (SHR) fed excess sodium, 16 Dahl 17 salt-sensitive rats (Dahl S), and in the two-kidney, one clip Goldblatt model. 18 The mechanisms of both the hypertensive effect of excess dietary sodium and the protective effect of potassium remain unknown.…”
mentioning
confidence: 99%